Threading Granules in Freiburg: 2nd International Symposium on “One Mitochondrion, Many Diseases – Biological and Molecular Perspectives”, a FRIAS Junior Researcher Conference, Freiburg im Breisgau, Germany, March 9th/10th, 2016 - Ralf J. Braun; Ralf M. Zerbes; Florian Steinberg; Denis Gris; Verónica I. Dumit (Microbial Cell)
Altered mitochondrial activities play an important role in many different human disorders, including cancer and neurodegeneration. At the Freiburg Institute of Advanced Studies (FRIAS) Junior Researcher Conference “One Mitochondrion, Many Diseases – Biological and Molecular Perspectives” (University of Freiburg, Freiburg, Germany), junior and experienced researches discussed common and distinct mechanisms of mitochondrial contributions to various human disorders.